Strategi Pemberdayaan Masyarakat Muslim di Perbatasan Antarnegara melalui Bimbingan dan Konseling Keagamaan - Syarifah Aminah; Sri Hidayati; Fitri Kusumayanti (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
STRATEGIES FOR EMPOWERING MUSLIM COMMUNITIES IN BORDER AREAS THROUGH RELIGIOUS GUIDANCE AND COUNSELING. There are three provinces in Kalimantan with international border areas. These border areas are among those classified as “3T” areas underdeveloped, frontier areas, and outermost area. There are two distinct types of Muslim communities in the international border villages in Sambas Regency. First, there are the Muslim-majority communities, such as in Temajuk Village, Paloh District. Second, there are also the Muslim-minority convert Dayak communities, such as in Kaliau and Sebunga Villages of Sajingan Besar District. To empower these convert communities, a religious guidance and counseling program, focusing on religious tolerance is carried out among these international frontier areas. From these empowerment programs, participants become more knowledgeable about religious moderation, which can later be implemented in the guidance process for other convert. Both religious guidance and counseling skill training, as well real practice are performed during the program to the convert communities.